Interstellar Now! Missions to Explore Nearby Interstellar Objects. Issue 1 (1st January 2022) - Hein, Andreas M.; Eubanks, T. Marshall; Lingam, Manasvi; Hibberd, Adam; Fries, Dan; Schneider, Jean; Kervella, Pierre; Kennedy, Robert; Perakis, Nikolaos; Dachwald, Bernd
Highlights: Flybys, rendezvous, and sample return missions to interstellar objects are shown to be feasible. Fast flybys are feasible with existing technologies. Rendezvous, sample return missions require solar electric propulsion, nuclear thermal propulsion. Abstract: The recently discovered first hyperbolic objects passing through the Solar System, 1I/'Oumuamua and 2I/Borisov, have raised the question about near term missions to Interstellar Objects. In situ spacecraft exploration of these objects will allow the direct determination of both their structure and their chemical and isotopic composition, enabling an entirely new way of studying small bodies from outside our solar system. In this paper, we map various Interstellar Object classes to mission types, demonstrating that missions to a range of Interstellar Object classes are feasible, using existing or near-term technology. We describe flyby, rendezvous and sample return missions to interstellar objects, showing various ways to explore these bodies characterizing their surface, dynamics, structure and composition. Their direct exploration will constrain their formation and history, situating them within the dynamical and chemical evolution of the Galaxy. These mission types also provide the opportunity to explore solar system bodies and perform measurements in the far outer solar system.